Sosialisasi Sistem Pengelolaan Sampah kepada Anggota Bank Sampah Berkah Nyata Desa Pandes - Bagus Prasetiyo, Angger; Ayuhikmatin Sekarjati, Kartinasari (ReTII, 2022)
The greatest threat that every nation in the world is currently facing is the garbage problem. The accumulation of improperly handled garbage has various negative effects. In order for the members of the Pandes Village Real Blessing Garbage Bank to provide output that is consistent with expectations, this service attempts to educate and practice trash management. This service educates members of the Pandes Village Real Berkah Trash Bank through lectures, questionnaires, and practice. The Pandes Village Hall Hall hosted the events on the first day, while the Real Blessings Multipurpose Room hosted them on the second. implementation of waste management system and machine maintenance-related tasks on the first day of material delivery. Participants will learn waste management techniques as well as how to maintain and repair waste processing equipment on the second day. According to the evaluation, there has been an improvement in the Real Berkah Waste Bank members' skills and expertise. The Real Berkah Berkah Waste Bank can serve as a model for other communities by implementing this service program, which will help all of its residents understand the value of keeping the environment clean